Utilization of Facebook Group Application as an Online Learning Media in Akidah Akhlak Learning - Muhamad Ali Hasymi Rafsanjani Tanjung; Nur Latipah; Alfi Alfarezi (Journal of Multidisciplinary Sustainability Asean, 2024)
Background. Technology has an important role in learning media, including the use of Facebook Group applications as online learning media. This study focuses on learning Aqidah Akhlak at Darussalam Dharmasraya Islamic Boarding School. Purpose. This study aims to explore the use of Facebook Groups as an online learning medium, identify the advantages and obstacles faced, and measure their effectiveness in increasing students' understanding of Aqidah Akhlak subjects. Method. This research uses quantitative methods with survey models and in-depth interviews. The survey was conducted online with 20 teachers as respondents, and an in-depth interview was conducted with one of the teachers who used Facebook Groups in learning. Results. The results showed that the use of Facebook Groups in learning Aqidah Akhlak was very effective. As many as 100% of teachers understand how to use this application, and 70% agree that Facebook Groups are very useful as a learning medium. However, there are several obstacles such as the need for internet quota and a stable network. Conclusion. Facebook groups as online learning media are very helpful for the teaching and learning process, especially in increasing students' understanding and enthusiasm for learning. Despite some technical obstacles, the app remains an effective solution in distance learning. The research suggests that the use of Facebook Groups be further integrated into the learning curriculum to maximize the benefits of technology in education.